Niche players: Spermatogonial progenitors marked by GPR125 - Seandel, Marco (2007)
The undifferentiated spermatogonia of adult mouse testes are composed of both true stem cells and committed progenitors. It is unclear what normally prevents these adult germ cells from manifesting multipotency. The critical elements of the spermatogonial stem cell niche, while poorly understood, are thought to be composed of Sertoli cells with several other somatic cell types in close proximity. We recently discovered a novel orphan G-protein coupled receptor (GPR125) that is restricted to undifferentiated spermatogonia within the testis. GPR125 expression was maintained when the progenitor cells were extracted from the in vivo niche and propagated under growth conditions that recapitulate key elements of the niche. Such conditions preserved the ability of the cells to generate multipotent derivatives, known as multipotent adult spermatogonial derived progenitor cells (MASCs). Upon differentiation, the latter produced a variety tissues including functional endothelium, illustrating the potential applications of such cells. Thus, GPR125 represents a novel target for purifying adult stem and progenitors from tissues, with the goal of developing autologous multipotent cell lines.